S‐NPP VIIRS thermal emissive bands on‐orbit calibration and performance. Issue 18 (22nd September 2014) - Efremova, Boryana; McIntire, Jeff; Moyer, David; Wu, Aisheng; Xiong, Xiaoxiong
Abstract Presented is an assessment of the on‐orbit radiometric performance of the thermal emissive bands (TEB) of the Suomi National Polar‐orbiting Partnership (S‐NPP) Visible Infrared Imaging Radiometer Suite (VIIRS) instrument based on data from the first 2 years of operations—from 20 January 2012 to 20 January 2014. The VIIRS TEB are calibrated on orbit using a V‐grooved blackbody (BB) as a radiance source. Performance characteristics trended over the life of the mission include the F factor—a measure of the gain change of the TEB detectors; the Noise Equivalent differential Temperature (NEdT)—a measure of the detector noise; and the detector offset and nonlinear terms trended at the quarterly performed BB warm‐up cool‐down cycles. We find that the BB temperature is well controlled and stable within the 30mK requirement. The F factor trends are very stable and showing little degradation (within 0.8%). The offsets and nonlinearity terms are also without noticeable drifts. NEdT is stable and does not show any trend. Other TEB radiometric calibration‐related activities discussed include the on‐orbit assessment of the response versus scan‐angle functions and an approach to improve the M13 low‐gain calibration using onboard lunar measurements. We conclude that all the assessed parameters comply with the requirements, and the TEB provide radiometric measurements with the required accuracy.